Development of functionalized abamectin poly(lactic acid) nanoparticles with regulatable adhesion to enhance foliar retention. Issue 19 (13th February 2017) - Yu, Manli; Yao, Junwei; Liang, Jie; Zeng, Zhanghua; Cui, Bo; Zhao, Xiang; Sun, Changjiao; Wang, Yan; Liu, Guoqiang; Cui, Haixin
Abstract : Functionalized abamectin poly(lactic acid) nanoparticles with different adhesion abilities to crop foliage can regulate folia retention of abamectin. Abstract : Pesticides are important to defend against biological disasters and ensure food security. Most conventional pesticide formulations suffer from heavy losses to the surrounding environment and low effective utilization rate, leading to the pollution of ecological systems and food because of their weak adhesion to crop foliage. To increase both the adhesion to foliage and effective utilization rate of pesticides, we developed three types of functionalized abamectin poly(lactic acid) (Abam-PLA) nanoparticles (CH3 CO-PLA-NS, HOOC-PLA-NS and H2 N-PLA-NS) with different adhesion abilities to cucumber foliage. The Abam-PLA nanoparticles were spherical with diameters of around 450 nm, and their maximum abamectin loading rate was around 50%. The nanoparticles exhibited better continuous release behavior and photostability compared with active abamectin. The Abam-PLA nanoparticles showed favorable deposition on the surface of cucumber foliage, and their adhesion to cucumber foliage surface followed the order: H2 N-PLA-NS > CH3 CO-PLA-NS > HOOC-PLA-NS. The adhesion of the nanoparticles to the foliage surface strongly depended on the functional groups on the nanoparticle surface. H2 N-PLA-NS interacted with the cucumber foliage surface by hydrogen bond, electrostatic attraction, and covalent bond. In contrast, HOOC-PLA-NS interacted with the cucumber foliage through hydrogen bond and electrostatic repulsion. Regulatable adhesion could be achieved by tuning the interaction mode between the nanoparticles and foliage surface. This study provided a visual method to better understand the interaction mechanism between nanoparticles and crop foliage. Our results will be helpful to develop pesticide nanoparticles with strong adhesion to foliage, improving the effective utilization rate and bioavailability of pesticides.